All Days 2002
DOI: 10.2118/73705-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidizing Additives on Formation Permeability During Matrix Treatments

Abstract: Matrix acidizing treatments are performed to increase the permeability of oil and gas formations and to remove various types of damage. Mineral acids, organic acids and chelating agents are used to stimulate carbonate formations and to remove damage. Sandstone formations are usually treated with mineral acids (usually containing some HCl and HF) to remove damaging solids or liquids. Usually, stimulation in sandstone is not achieved. While a reactive fluid must be present to dissolve the damage or to remove par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…More recently, Dabbousi et al (1999) andNasr-El-Din et al (2002) showed that acidizing additives may affect dissolution of some types of scale or cause changes in the surface tension of the fluids. Frenier and Hill (2002) used linear core flood and rotating disk tests to investigate if the use of some additives such as corrosion inhibitors, surfactants, and solvents can cause damage to the formations due to adsorption or precipitation, alter the acid effectiveness in removal the damage, or change the dissolution mechanisms. The authors reached a general conclusion that acid additives that are highly soluble in the stimulation fluid, such as surfactants, have minimal effect on the performance of the fluid or on formation damage.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Dabbousi et al (1999) andNasr-El-Din et al (2002) showed that acidizing additives may affect dissolution of some types of scale or cause changes in the surface tension of the fluids. Frenier and Hill (2002) used linear core flood and rotating disk tests to investigate if the use of some additives such as corrosion inhibitors, surfactants, and solvents can cause damage to the formations due to adsorption or precipitation, alter the acid effectiveness in removal the damage, or change the dissolution mechanisms. The authors reached a general conclusion that acid additives that are highly soluble in the stimulation fluid, such as surfactants, have minimal effect on the performance of the fluid or on formation damage.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32] The dissolution rate was calculated from the slope of the first few points in plots of calcium concentration and reaction time. The initial surface area of the disk was also used to determine the dissolution rate.…”
Section: Measurements Of Calcite Dissolution Ratementioning
confidence: 99%
“…This instrument has been extensively used to investigate the reaction of acids and chelating agents with carbonate rocks. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] It has been also used to study mass and heat transfer into non-Newtonian fluids. [16][17][18] The reaction between acid and rock is a three-step process involving:…”
Section: Introductionmentioning
confidence: 99%
“…While iron (III) in solution can reduce calcite dissolution rate at low rotational speeds as it is likely that iron (III) hydroxide forms a surface layer that can not be removed at low speeds, at high concentrations and high rotational speeds, it can increase significantly the dissolution rate of calcite. While some have observed that mutual solvent (10 vol% EGMBE) in acid solution can increase the dissolution rate significantly (Jordan et al 2002;Taylot et al 2004), others have not observed any noticeable changes (Frenier and Hill 2002). Corrosion inhibitor, a quaternary amine, has been shown to reduce calcite dissolution rate.…”
Section: Introductionmentioning
confidence: 99%